Jagged1 modulated tumor-associated macrophage differentiation predicts poor prognosis in patients with invasive micropapillary carcinoma of the breast. Issue 16 (April 2017) - Liu, Hang; Wang, Jingxuan; Liu, Zhaoliang; Wang, Le; Liu, Shoujun; Zhang, Qingyuan
Abstract: Objectives: Invasive micropapillary carcinoma of the breast (IMPC) constitutes a unique and aggressive subtype of breast cancer. We aimed to evaluate the prognostic significance of the Jagged1 (a ligand of the Notch pathway) expression, and infiltration density of tumor-associated macrophages (TAMs) in patients with IMPC. Methods: Jagged1 expression and CD163+, CD68+ macrophage infiltration were evaluated by immunohistochemistry in 222 tumor samples, and the clinical significance was analyzed. mRNA level of Jagged1 was analyzed by real time PCR in tumor tissues. Results: The IMPC patients showed larger tumor size, more lymphatic invasion, higher expression levels of estrogen receptor (ER), increased Ki67 index, higher Jagged1 protein level, and denser infiltration of CD163+ macrophages compared to patients with invasive breast ductal carcinoma. In the IMPC cohort, positive Jagged1 expression was related to aggressive features including large tumor size, lymphatic invasion, and Ki67 overexpression. Statistical significance was found between CD163+ macrophage infiltration and Jagged1 expression levels. Cox regression analysis revealed that ER negativity, positive Jagged1 expression, and a high degree of CD163+ macrophage infiltration were independent prognostic factors for disease-free survival, and positive Jagged1 expression was an independent prognostic factor for overall survival. The level of Jagged1 mRNA was higher in tumor tissues of patients with IMPC. Conclusion: Jagged1, by modulating TAMs infiltration, is associated with a less favorable prognosis for patients with IMPC. Our results have important implications for therapies targeting Jagged1-Notch signaling and re-educating TAMs polarization for patients with IMPC.